Anti-Implantation Activity of Kepel (Stelechocarpus burahol) Pulp Ethanol Extract in Female Mice - Suparmi Suparmi; Israhnanto Isradji; Iwang Yusuf; Dina Fatmawati; Idiah Hapsari Ratnaningrum; Shamrotul Fuadiyah; Indra Indra Wahyuni1; Dini Amelia Rahmah (The Journal of Pure and Applied Chemistry Research, 2015)
Kepel (Stelechocarpus burahol) has been used as a contraceptive remedy in Indonesia traditional Javanese royal family. It fruit contains a toxic substances to fetus. However, few studies have been conducted on the toxic effect of kepel fruit. This paper is disclosed the effect of kepel’s fruit extract on the percentage of fetus death, ovaries weight, and endometrial thickness in female mice. This study applied a post-test control group design. A 28 female of mice were divided into 4 groups. Group I (control), II, III, and IV were groups treated with kepel pulp extract using dosage 0.65, 1.30, and 3.60 mg/kg body weight (BB). The extract was dissolved in DMSO and given in 1.0 mL/mouse. The result gives implantation numbers of each group I-VI were 5.60±1.14; 6.20±1.64; 7.60±1.51; and 8.00±1.58, respectively. The percentages of fetus death 0.00%±0.00; 48.89%±22.78; 35.83%±25.27; and 30.87%±23.01 and fetus re-sorption in all groups were recorded as 0.00±0.00. Moreover, the ovaries weight of each groups I, II, III, and IV were recorded in 0.11±0.01; 0.08±0.01; 0.11±0.32; and 0.07±0.02 g, respectively. In addition, endometrial thickness were calculated as 584.86; 841.68; 659.72; and 624.10 µm. The anova test showed that insignificant difference for ovaries weight and endometrial thickness both for control and treated groups. Conversely, the LSD test showed the percentage of fetus death has a significant difference between control and treatment groups. These result suggest that kepel pulp ethanol extract has potency for anti-implantation.